Mazatlán as a Heterotopia of Retirement: Global Flows, Non-Places, and Deterritorialization in Expatriate Migration - García-Macías , Pascual; Zamora , Rodolfo García (Journal of Posthumanism, 2025)
This article examines the international migration of retired expatriates to Mazatlán, Mexico, through a critical theoretical framework that articulates the concepts of scapes (Appadurai), non-places (Augé), and heterotopias (Foucault). Drawing from poststructuralist and posthumanist approaches to space, identity, and globalization, the paper argues that the presence of North American retirees in Mazatlán is not merely a demographic trend but a complex reconfiguration of urban, social, and symbolic landscapes. Through the deterritorialized circulation of people (ethnoscapes), capital (financescapes), and imaginaries (ideoscapes), Mazatlán is increasingly inscribed into global geographies of retirement and lifestyle migration. These flows produce zones of comfort and cultural friction: gated communities, English-speaking enclaves, and foreign-run businesses emerge alongside traditional urban fabrics and local ways of life. The result is the creation of hybrid heterotopic spaces—material and symbolic islands where expatriates reimagine aging, privilege, and belonging. Based on ethnographic-style interviews with expatriates, this study explores how retired foreigners reproduce and negotiate cultural practices in a context marked by inequality, hospitality, and glocal transformation. The paper calls for a critical reflection on how posthuman mobility, affective geographies, and economic asymmetries reshape urban life and generate novel forms of spatial citizenship in the Global South.